Hearing the voices of children and young people to develop and test a patient-reported experience measure in a specialist paediatric setting. Issue 3 (13th September 2017) - Wray, Jo; Hobden, Sylvie; Knibbs, Sarah; Oldham, Geralyn
Abstract : Objective: To develop and test patient-reported experience measures (PREMs) for children and young people in a specialist paediatric hospital setting. Design: Six PREMs were developed and tested by children and young people for children and young people aged 8–11, 12–13 and 14–16 years in inpatient and outpatient settings. A week-long pilot was implemented across inpatient wards and outpatient clinics to identify facilitators and barriers to the routine use of PREMs in a real-time setting across our organisation. Setting: Tertiary paediatric hospital. Main outcome measures: Final PREMs; identified facilitators and barriers to implementation. Participants: 543 children and young people aged 8–16 years attending outpatient clinics or inpatient wards across a range of specialties. Results: Three key themes about hospital experience were identified during focus groups: facilities, treatment and tests and people working at the hospital, and these provided the structure for the questionnaires. During cognitive testing the questionnaires were generally understood but some revisions to language and length of the questionnaires were required. Two designs were selected for the final PREMs. During acceptability and feasibility testing it was evident that children and young people liked the PREMs and wanted to give feedback on their hospital experience. Particular challenges for routine use of the PREMs focused on sustainability and resources. Conclusions: The new PREMs will provide children and young people receiving care in specialist paediatric hospitals with the opportunity to provide feedback on their experience. Sustainability and ensuring that feedback results in improvements need to be addressed in future work.